Ready-to-eat cereal consumption is associated with improved nutrient intakes and diet quality in Canadian adults and children across income levels - Sanders, Lisa M.; Zhu, Yong; Jain, Neha; Normington, James; Holschuh, Norton; Nechanicky, Megan; Tucker, Michelle; Garcia-Bailo, Bibiana (Frontiers in Nutrition, 2024)
Background Results from observational studies suggest ready-to-eat cereal (RTEC) consumption is associated with higher diet quality. In the United States, studies have shown that RTEC is an important contributor to nutrient intakes across income levels. However, it is unknown if this association varies by income level in the Canadian population. Given its affordability, RTEC may represent an important source of nutrients for lower-income individuals. Objective This study evaluated the association of RTEC consumption with nutrient intakes and diet quality across household income levels in Canadian adults and children. Methods Income and dietary data from 24 h dietary recalls were obtained from the 2015 Canadian Community Health Survey (CCHS)—Nutrition in 6,181 children (2–18 years) and 13,908 adults (19+ years). Diet quality was assessed with a modified Nutrient Rich Food Index (NRF) 9.3. Income levels were stratified into low, middle, and high based on family size, and data were analyzed by RTEC consumption and income level using multivariate linear regression adjusted for energy, age, and sex. Results Diet quality was greater in adult and child RTEC consumers across all household income levels. Children and adults consuming RTEC also had higher nutrient intakes, including shortfall nutrients such as calcium, dietary fiber, iron, magnesium, and vitamin D. RTEC provided <10% of energy intake, <4% of saturated fat intake, and <9% of total sugar intake across all ages and income levels, while also providing one-third of daily iron intake and at least 10% of daily intake of dietary fiber, thiamin, folate, and vitamin B6. Conclusion RTEC consumption was associated with improved nutrient intakes and diet quality in adults and children across household income levels. Nutrient dense and affordable food choices, such as RTEC, may be a helpful strategy to improve the diet quality of Canadians, particularly those with a lower household income.